PENGEMBANGAN USAHA DAUN SIRIH DI KUOK KABUPATEN KAMPAR - Afiah Afiah; Syafriani Syafriani; Nia Aprilla (COVIT (Community Service of Health), 2021)
Betel leaf production in Riau Province has increased from year to year accompanied by an increasing number of plantings. In 2010 with a productivity of 2 tons, while in 2011 with a productivity of 4 tons. With betel leaf producers in Riau Province covering 10 districts/cities namely Indragiri Hulu, Indragiri Hilir, Pelalawan, Siak, Kampar, Rokan Hulu, Rokan Hilir, Bengkalis, Pekanbaru and Dumai. (BPS Province Roau, 2011). The purpose of this activity is to find innovative ideas, increase creativity, instill an entrepreneurial spirit, train mentally and teach to work hard and be responsible. In addition, another goal is to reduce the waste generated by processing them into betel leaf chips, and betel leaf candy. There are several obstacles faced, namely (1) Limited capital. (2) Low motivation for entrepreneurship with betel leaf as the main ingredient. (3) There is no diversity of processed betel leaf products. (4) The absence of packaging and marketing of betel leaf. Activities that will be carried out in this PKM program include several development efforts, including betel leaf chips. The cost of profit from the sale of processed betel leaf products for betel leaf chips is sold at a price of Rp. 20,000 per pack after calculating the manufacture of betel leaf chips of Rp. 10,000, and then betel leaf candy is sold at a price of Rp. 10,000 per pack after calculating the manufacture of betel leaf candy of Rp. 8,000. So that development efforts can increase the income of betel farmers partners.